We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
-1
170
1
avatar+123 

4. Solve the following system of equations:

3 + 2x - y = 0,

-3 - 7y = 10x

 

by using substitution, and by elimination.

 Feb 24, 2019

Best Answer 

 #1
avatar+6045 
+1

\(2x - y = -3\\ 10x+7y = -3\)

 

\(\text{substitution}\\ y = 2x+3\\ 10x+7(2x+3) = -3\\ 24x+ 21=-3\\ 24x=-24\\ x=-1, y = 1\\ --\\ \text{elimination}\\ \text{subtract 5x the first equation from the second}\\ 12y=12\\ y=1,~x=-1\)

.
 Feb 24, 2019
 #1
avatar+6045 
+1
Best Answer

\(2x - y = -3\\ 10x+7y = -3\)

 

\(\text{substitution}\\ y = 2x+3\\ 10x+7(2x+3) = -3\\ 24x+ 21=-3\\ 24x=-24\\ x=-1, y = 1\\ --\\ \text{elimination}\\ \text{subtract 5x the first equation from the second}\\ 12y=12\\ y=1,~x=-1\)

Rom Feb 24, 2019

13 Online Users

avatar